Experience quality in moderating lifestyle, brand awareness and taste quality on repurchase - Febrianti Febrianti; Surya Bintarti; Iin Masriah (Junal Ilmu Manajemen, 2023)
As a result of the COVID-19 pandemic, a person's lifestyle has undergone many changes, and continues to develop with a healthy lifestyle during the pre-pandemic era as it is today. The end of the Covid-19 pandemic has had a positive impact on healthy lifestyle habits in the lives of every individual in society. Healthy living habits by consuming nutritious food and balanced drinking water according to the body's needs play an important role in fulfilling a healthy lifestyle pattern. Drinking water is a fundamental basic need for humans, this problem is the reason for the emergence of many companies that contribute to the production of practical bottled drinking water. This study aims to examine the quality of experience in moderating consumer lifestyle, brand awareness, and taste quality on consumer repurchase decisions. The number of respondents in this study were 100 respondents who had purchased or consumed Pristine 8.6+ mineral water in the Bekasi Regency area. The collection of the population in this study is non-probability sampling and the sampling technique for respondents is purposive. This research method uses quantitative methods. This research was processed using a regression technique, which was processed using SmartPLS Software.This study proves that lifestyle and brand awareness have a positive and significant effect on Repurchase while taste quality has a negative and insignificant effect on Repurchase. Experience quality in moderating brand awareness lifestyle and taste quality on Repurchase of Pristine8,6+ products has no effect on Repurchase so it has a negative and insignificant effect.